TRADISI KEPUNGAN TUMPENG TAWON DESA MANGUNWENI KECAMATAN AYAH KABUPATEN KEBUMEN: KAJIAN FOLKLOR - Sulastri, Yosi; Apriyani, Tristanti (Universitas Ahmad Dahlan, 2021)
This research is motivated by the existence of oral literature on the tradition of the tumpeng wasp siege that has not been documented in Mangunweni Village, Ayah District, Kebumen Regency. Oral literature has information that can be utilized by the public. Through documentation, this information can be opened and used so that the objectives of describing oral literature, deciphering the value of oral literature, and identifying the function of oral literature can be achieved. The theory used in this research is the theory of the function of folklore by William R. Bascom and the theory of folklore proposed by Ruth Finnegan that oral literature has value in the phenomenon of human culture.The formal object of this research is the form, function, and value of oral literature. The material object in this study is oral literature in the tradition of the tumpeng wasp siege of the people of Mangunweni Village, Ayah District, Kebumen Regency. The analysis technique used is qualitative data analysis conducted by induction.The results obtained from this study are: 1) the oral literature of theÂ tumpeng tawonsiege tradition is a type of oral tradition in the form of myths and folk beliefs; 2) the values contained in the tumpeng wasp siege tradition consist of divine values, harmony between humans, equality between humans, diversity, sincerity, unyielding, usefulness to others, and concern in achieving goals; 3) the tumpeng wasp siege tradition has a function as a projection system, as a tool for ratifying cultural institutions and institutions, as an educational tool (pedagogical device), and as a coercive and supervisory tool so that community norms will always be obeyed by members.